Colibacillary arthritis and severe osteomyelitis in lame goat kids due to management procedures. Issue 1 (7th January 2021) - Prins, Sander; Junker, Karin; Lievaart‐Peterson, Karianne; Sargison, Neil D.; Vellema, Piet
Abstract: Lameness in the hindquarters was seen in twenty goat kids out of a group of 90 on a dairy goat farm. Initial treatment with antibiotics and NSAID's did not improve the condition. At necropsy in eight kids, a multi‐resistant Escherichia coli was isolated from affected femurs, strongly indicative of colibaccilary osteomyelitis. In addition, with 573–915 mg/kg dry matter, liver copper concentrations were increased. Predisposing factors for osteomyelitis were poor colostrum quality, stress as a consequence of multiple simultaneous management procedures, preventive use of antibiotics, and elevated liver copper concentrations in the kids. To prevent future outbreaks, it was advised to improve colostrum management, reduce stress by spreading procedures such as vaccinations, disbudding, and dietary changes. Antibiotic treatments should be used only to treat individual kids, and not preventively. Elevated liver copper should be reduced by minimising the copper content in milk replacer.